STRATEGI PERLINDUNGAN ANAK DAN PEREMPUAN DI PAPUA SELATAN: ANALISIS TANTANGAN DAN SOLUSI - Sukirman, Sukirman; Tajuddin, Mulyadi Alrianto; Nurul Widhanita Y Badilla (The Juris, 2024)
This study aims to analyze protection strategies for children and women in South Papua using a qualitative approach through literature studies and in-depth interviews. Where the South Papua region, especially in Merauke Regency, faces significant challenges related to gender-based violence, limited access to education, and economic inequality. In the context of a strong patriarchal culture, women and children are often victims of domestic violence and underage marriage triggered by poverty, lack of education, and limited legal awareness. The results of this study found that the solutions that need to be implemented include strengthening special protection regulations, economic empowerment for women through entrepreneurship and community education campaigns to foster awareness of women's and children's rights. In addition, support and collaboration between the government, non-governmental organizations, and local communities are needed to overcome these challenges. The community approach is an important step in ensuring sustainable protection and creating a deep attitude towards gender-based violence and injustice faced by women and children in South Papua. This research is expected to contribute to providing policy recommendations that focus on empowerment, education and community-based approaches so as to improve the protection and quality of life of women and children in the South Papua region, especially in Merauke Regency.